Peer Assisted Study Sessions (PASS) preparing occupational therapy undergraduates for practice education: A novel application of a proven educational intervention. (26th September 2018) - Larkin, Helen; Hitch, Danielle
Abstract : Background/aim: With rapid growth in occupational therapy education programmes across Australia and a corresponding increase in demand for placements, there is a need to ensure that students are well prepared for practice education. An occupational therapy education programme at a Victorian university introduced a specific Peer Assisted Study Sessions (PASS) programme to develop students' preparedness for practice education, supplementing core and existing teaching activities. The aim of this study was to explore the experiences of occupational therapy students, including their perception of its impact on learning and preparation for practice education. Methods: Using a phenomenological approach, semi‐structured interviews were undertaken with 15 students who participated in PASS for Placement, 2 of whom were the student leaders. Interviews were transcribed verbatim and thematically analysed. Results: Seven themes emerged from the data: a safe environment; skill development; one of us; feeling connected; student‐centred and student‐led; different motivations; and learning through leading. Students were positive about the impact of the programme on their confidence and readiness for practice education. Student leaders also reported that it contributed to the development of leadership skills and overall levels of confidence regarding practice education. Conclusions: This study supports the use of PASS to promote practice education preparedness, as there were positive outcomes for both students and student leaders. However, it indicates that participation in such programmes should be voluntary rather than mandatory. This study addresses a clear gap both in current practice and research, describing the application of a proven educational intervention in a new and innovative way. It is the first reporting of the use of PASS to support the preparation of students for practice education in any health discipline and subject to feasibility studies, could be adopted more broadly by disciplines beyond health, where work integrated learning is a mandatory element of the education programme.